Bahasa Inggris - Dzikrul Rizki; Yusrizal Yusrizal; A. Halim; M. Syukri (Postgraduate, University of Mataram, 2023)
This learning model consists of five stages, namely: (1) Engagement (generating interest), (2) Exploration, (3) Explanation, (4) Extend (expansion), and (5) Evaluation. In fact, from the results of observations made at the SMA Negeri Unggul Subulussalam school, it was found that the motivation of students still low. The purpose of this study was to increase students' learning motivation by applying the 5E Learning Cycle model to sound wave material. This research is a quantitative research type of non-equivalent control group design experiment. The population used in this study was students of class XI IPA with a sample of 60 people taken by purposive sampling. This study uses two classes, namely the experimental class and the control class. The results showed that the average value of the control class was 55.61 in the low category and the average value of the experimental class was 82.26 in the very high category.